2020
DOI: 10.1111/mcn.13003
|View full text |Cite
|
Sign up to set email alerts
|

Review of policies, data, and interventions to improve maternal nutrition in Afghanistan

Abstract: Malnutrition contributes to direct and indirect causes of maternal mortality, which is particularly high in Afghanistan. Women's nutritional status before, during, and after pregnancy affects their own well‐being and mortality risk and their children's health outcomes. Though maternal nutrition interventions have documented positive impact on select child health outcomes, there are limited data regarding the effects of maternal nutrition interventions on maternal health outcomes globally. This scoping review m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Proper nutrition and healthy eating habits are essential for survival, physical development, mental health, performance, and overall health (Khan, Khanlou, et al, 2018 ), whereas household food insecurity leads to poor physical and mental health, frequent hospitalizations, and premature deaths of infants (Hutchinson & Tarasuk, 2022 ). Maternal nutrition involves nutrition during antenatal or postnatal stages and also the time before conception and even starting from adolescence when early childbearing is normal (Kim et al, 2020 ). Adolescent population mostly experiences nutritional challenges, which strongly impacts their growth and development (Kumar, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proper nutrition and healthy eating habits are essential for survival, physical development, mental health, performance, and overall health (Khan, Khanlou, et al, 2018 ), whereas household food insecurity leads to poor physical and mental health, frequent hospitalizations, and premature deaths of infants (Hutchinson & Tarasuk, 2022 ). Maternal nutrition involves nutrition during antenatal or postnatal stages and also the time before conception and even starting from adolescence when early childbearing is normal (Kim et al, 2020 ). Adolescent population mostly experiences nutritional challenges, which strongly impacts their growth and development (Kumar, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Refugees face a high risk of malnutrition due to poor socioeconomic status, food insecurity, and insufficient health‐care facility (Saeedullah et al, 2021 ). Malnutrition is directly or indirectly responsible for maternal mortality and is particularly high in Afghanistan (Kim et al, 2020 ). Afghans are staunch Muslims (Malik et al, 2019 ), and Afghan women are less educated than men, marry at a young age, and have many babies until a boy is born (Smith, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Future nutrition interventions should therefore be tailored to the specific needs and context of the target population. Furthermore, the study re-enforces, existing body of evidence indicating that maternal focused interventions particularly those with a multi-sectoral nature contribute to improved maternal diet diversity, micronutrient intake and overall nutritional status [29][30][31].…”
Section: Discussionmentioning
confidence: 60%
“…In 2018, Lesotho had made substantial progress in the maternal and child nutrition surveillance policy, but it needed to increase investment in capacity strengthening of national food and nutrition offices, and enhanced collaboration with the agricultural department (Mugomeri, 2018 ). In 2020, a review reported that maternal anaemia interventions were incorporated in Afghanistan's health and nutrition‐related policies, however, the government did not develop specific goals to measure effectiveness (Kim, 2020 ).…”
Section: Introductionmentioning
confidence: 99%